Research and application of advanced oxidation technology for low carbon and harmless treatment of hospital wastewater - XIONG Zhaokun; GU Lingyun; WANG Xinhao; CHEN Kexin; LAI Bo* (能源环境保护)
The presence of emerging contaminants such as antibiotics, endocrine disruptor in hospital wastewater makes it difficult to effectively remove through conventional processes. Simultaneously, in the context of the frequent occurrence of infectious diseases, the disinfection capacity for pathogenic microorganisms in hospital wastewater needs improvement urgently. In recent years, researchers have explored advanced oxidation technologies to effectively degrade pharmaceutical contaminants like antibiotics in hospital wastewater, achieving simultaneous inactivation of pathogens. However, the high cost, substantial energy consumption, and the potential generation of additional toxic by-products limit the widespread application of advanced oxidation technologies in practical engineering. This article provides a review of the current research status on the use of advanced oxidation technologies for treating hospital wastewater, introducing techniques such as Fenton oxidation, persulfate activation, peracetic acid oxidation, ozone oxidation, electrochemical oxidation, and presenting an overview of electrochemical-based synergistic catalytic oxidation technologies. Furthermore, it summarizes the advanced oxidation treatment processes and equipment for the low-carbon and harmless treatment of actual hospital wastewater. Finally, this review analyzes the current challenges in the low-carbon and harmless treatment of hospital wastewater and provides insights into future research directions in China.